Current and Future Approaches for Diagnosing Small Intestinal Dysbiosis in Patients With Symptoms of Functional Dyspepsia - Shah, Ayesha; Talley, Nicholas J.; Holtmann, Gerald (Frontiers in Neuroscience, 2022)
The development and application of next generation sequencing technologies for clinical gastroenterology research has provided evidence that microbial dysbiosis plays an important role in the pathogenesis of both intestinal and extra-intestinal diseases. Microbial dysbiosis is characterized as alterations of diversity, function, and density of the intestinal microbes. There is emerging evidence that alterations of the gastrointestinal microbiome plays a role in the pathophysiology of a variety of functional gastrointestinal conditions including irritable bowel syndrome (IBS) and functional dyspepsia (FD),also known as disorders of brain-gut axis interaction. Clinicians have for many years recognized that small intestine bacterial overgrowth (SIBO) is typified by a microbial dysbiosis that is underpinned by abnormal bacterial loads in these sites. SIBO presents with symptoms which overlap with symptoms of FD and IBS, making it unclear if it the cause or consequence in relation to functional gastrointestinal disorders (FGIDs). More recently, new terms including ‘intestinal methanogen overgrowth’ and ‘small intestinal fungal overgrowth’ have been introduced to emphasize the contribution of methane production by archaea and fungi in small intestinal dysbiosis. There is emerging data that targeted antimicrobial treatment of SIBO in patients with FD with or without concomitant IBS, results in symptom improvement and normalization of positive breath tests. However, the association between SIBO and FGIDs remains controversial, mainly due to the lack of valid and universally accepted diagnostic tests for SIBO. Culture of jejunal fluid aspirate has been considered the ‘traditional gold standard’ for establishing the diagnosis of SIBO. However, this technique is invasive, prone to cross contamination from oropharyngeal and luminal microbes, and there is controversy regarding the best cut off values for SIBO diagnosis, hence it is rarely used in routine clinical settings. These limitations have led to the development of breath tests, which when compared with the ‘traditional gold standard’, have sub-optimal sensitivity and specificity for SIBO diagnosis. With newer diagnostic approaches – based upon applications of the molecular techniques there is an opportunity to characterize the duodenal and colonic mucosa associated microbiome and associated gut microbiota dysbiosis in patients with various gastrointestinal and extra-intestinal diseases.